Kartagener Syndrome with Pan Atopic Airway Disease - Aakanksha; Saby Anna Kunjumon; Ketaki Vasudeo Utpat; Unnati Desai; Ramesh Bharmal (Wolters Kluwer Medknow Publications, 2022)
Kartagener syndrome (KS) is a rare type of primary ciliary dyskinesia, which comprises a triad of chronic sinusitis, situs inversus, and bronchiectasis. It has a heterogeneous inheritance, mainly inherited as an autosomal recessive disorder, causing functional defect in ciliary movement. Bronchial asthma (BA) is a disease where there is a chronic inflammation of airways along with hyperreactive airways with variable airflow obstruction. We are reporting a case of a 36-year-old man with chronic sinusitis, situs inversus totalis, bronchiectasis, and well-controlled asthma. This case report orients toward the fact that KS can present with BA which makes this case idiosyncratic. Moreover, the veracious takeaway lesson is that early diagnosis will improve the quality of life of the patients and reduce the complexities of the disease, thus will bring down the morbidity and mortality of the patients.